Analysis of factors associated with profitability of Kazakhstani state hospitals and polyclinics. - Shayakhmetov, Yerassyl (Nazarbayev University School of Medicine, 2018)
The following study analyzed factors affecting profitability of medical state enterprises. The primary interest of the study was the effect of corporate governance on financial performance of oblast level hospitals and primary care clinics. It was found that the presence of a supervisory board for the hospital or clinic is associated with decreased probability of producing net positive income (37% less chance) in these organizations. Also it was found that characteristics of supervisory boards like number of people in the board and meetings held by supervisory boards are not associated with profitability of state medical enterprises. The profitability of state medical organizations also differed between regions of the country and between organizations located in cities and rural regions.
Keywords: state hospitals; polyclinics